Environmental change influences the life history of salmon Salmo salar in the North Atlantic Ocean. Issue 2 (3rd January 2016) - Jonsson, B.; Jonsson, N.; Albretsen, J.
Abstract : Annual mean total length ( L T ) of wild one‐sea‐winter (1SW) Atlantic salmon Salmo salar of the Norwegian River Imsa decreased from 63 to 54 cm with a corresponding decrease in condition factor ( K ) for cohorts migrating to sea from 1976 to 2010. The reduction in L T is associated with a 40% decline in mean individual mass, from 2 to 1·2 kg. Hatchery fish reared from parental fish of the same population exhibited similar changes from 1981 onwards. The decrease in L T correlated negatively with near‐surface temperatures in the eastern Norwegian Sea, thought to be the main feeding area of the present stock. Furthermore, S. salar exhibited significant variations in the proportion of cohorts attaining maturity after only one winter in the ocean. The proportion of S. salar spawning as 1SW fish was lower both in the 1970s and after 2000 than in the 1980s and 1990s associated with a gradual decline in post‐smolt growth and smaller amounts of reserve energy in the fish. In wild S. salar, there was a positive association between post‐smolt growth and the sea survival back to the River Imsa for spawning. In addition, among smolt year‐classes, there were significant positive correlations between wild and hatchery S. salar in L T, K and age at maturity. The present changes may be caused by ecosystem changes following the collapse and rebuilding of the pelagic fish abundance in the North Atlantic Ocean, a gradual decrease in zooplankton abundance and climate change with increasing surface temperature in the Norwegian Sea. Thus, the observed variation in the life‐history traits of S. salar appears primarily associated with major changes in the pelagic food web in the ocean.